Advantages of the Microwave Tool in Organophosphorus Syntheses - Keglevich, György; Kiss, Nóra Zsuzsa; Grün, Alajos; Bálint, Erika; Kovács, Tamara (Synthesis, 2017)
The microwave (MW) technique has become an important tool also in the organophosphorus field of organic chemistry. On the one hand, otherwise reluctant reactions, such as the esterification of P-acids, may be enhanced by the effect of MW, while on the other hand, catalysts may be omitted, or catalyst systems may be simplified on MW irradiation. This later group includes the Kabachnik–Fields reactions, alkylation of active methylene-containing compounds, O-alkylations, deoxygenations, as well as the Hirao reaction. It is also the purpose of this review to elucidate the scope and limitations of the MW tool, to interpret the MW effects, and to model the distribution of local overheatings and their beneficial effect.1 Introduction2 The Esterification of Phosphinic Acids2.1 Synthetic Results2.2 Scope and Limitation of the Application of MWs2.3 Modelling the Distribution of the Local Overheatings and Predicting Their Effect3 The Simplification of Catalytic Systems3.1 Replacement of the Catalyst by MW Irradiation3.1.1 The Kabachnik–Fields Reaction3.1.2 Solid–Liquid Phase Alkylation of Active Methylene-Containing Compounds3.1.3 Solid–Liquid Phase Alkylation of Phosphinic Acids3.1.4 The Deoxygenation of Phosphine Oxides3.2 The Hirao Reaction without Added P-Ligands4 Conclusions
Keywords: organophosphorus chemistry; microwave irradiation; phosphinates; Kabachnik–Fields reaction; alkylation, deoxygenation; Hirao reaction